Impact of Covid-19 Pandemic on FDI in Nepal - Regmi, Krishna Kumar (The Lumbini Journal of Business and Economics, 2023)
Foreign Direct Investment (FDI) and Foreign Aid is an essential source of economic development for developing countries. However, FDI depends on the economic environment, as do other development assistance depends on the country’s foreign diplomacy and relation. The study aims to find the impact of Covid-19 on FDI,inflow and other barriers for receiving FDI commitment in Nepal. The study is descriptive and analytical. Secondary data are used in the study. The Covid-19 pandemic has reduced FDI commitments funds as envisioned. However, pandemic is not the only barrier of investment commitment. Still, there are barriers such as business environment, poor infrastructure, lack of skilled human resource, political transitions, weak governance, natural calamities, and tax slab which are critical in Nepal. Although FDI in Nepal was in an upward trajectory till 2019, the COVID-19 pandemic has reduced it as the primary economic development source of Nepal.